The Human CMV IE1 Protein: An Offender of PML Nuclear Bodies - Scherer, Myriam; Schilling, Eva-Maria; Stamminger, Thomas (Advances in Anatomy Embryology and Cell Biology, 2017)
PML nuclear bodies (PML-NBs) are SUMOylation-dependent, highly complex protein assemblies that accumulate in the interchromosomal territories of the cell nucleus. Research of the last two decades revealed that many viruses have evolved effector proteins that modify PML-NBs. This correlates with antagonization of individual PML-NB components which act as host cell restriction factors. The multifunctional immediate-early protein IE1 of human cytomegalovirus directly interacts with the PML protein resulting in a disruption of the dot-like structure of PML-NBs. This review summarizes recent advances on the functional consequences of PML-NB modification by IE1. In particular, we describe that PML exerts a novel co-regulatory role during the interferon response which is abrogated by IE1. Via binding to PML, IE1 is able to compromise both intrinsic antiviral defense mechanisms and classical innate immune responses. These interactions of IE1 with innate host defenses are crucial for the onset of lytic replication and, consequently, may represent promising targets for antiviral strategies.
EVALuna2:35297